IDENTIFIKASI WASTE DEFECT DENGAN VALSAT DAN PEMBUATAN JADWAL MAINTENANCE UNTUK MENINGKATKAN AVAILABILITY DAN MENGURANGI DEFECT. - Irma Agustiningsih Imdam; Muhammad Aqsho; Juliansyah Aristama; Nico Sachzehan (Politeknik Negeri Batam, 2025)
This research aims to identify and minimize waste in the join maple production process at PT MNO, an IKM (small and medium industry) company operating in the automotive component sector. A lean manufacturing approach was applied using Value Stream Mapping (VSM) to analyze the overall production flow. Furthermore, a Waste Assessment Questionnaire (WAQ) followed by a Waste Relationship Matrix (WRM) was used to determine the most dominant type of waste. The results indicate that defect waste is the main problem, leading to increased production time due to additional rework activities. Three types of defects were identified in join maple products, namely burnt defects, small head dimensions, and burr defects. The VALSAT approach using Quality Filter Mapping (QFM) revealed that burr defects were the most dominant, occurring in the cutting process at a rate of 1.26%, exceeding the company standard of 1%. Based on fishbone diagram analysis, the main causes of burr defects include corrective maintenance practices, the absence of a periodic tool replacement schedule, and weak implementation of the 5S/5R culture. The proposed improvements include daily tool inspections as preventive maintenance, the use of inspection check sheets, scheduled tool replacement, and the application of jidoka. The results show that the defect rate decreased from 1.26% to 0.88%, availability increased from 88% to 94%, performance efficiency rose from 63.76% to 80%, and quality improved from 98.73% to 99.34%, resulting in a 19.55% increase in Overall Equipment Effectiveness (OEE).